LEVERAGING FLASHCARD FOR ELT: A SYSTEMATIC REVIEW - Ziyan Annisah; Ghaniyah Nur Azeezah Putri; Nafan Tarihoran (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Flashcards in English Language Teaching (ELT) have gained significant attention due to their effectiveness in vocabulary acquisition, engagement, and retention. This systematic review aims to analyze existing studies on the role of flashcards in ELT, comparing traditional and digital formats and identifying their impact on language learning outcomes. The study follows a systematic literature review methodology, selecting 3.946 articles published (Connected Paper: 221, PubMed: 179, Science Direct: 507, Taylor: 1.670, Mendeley. Co: 1.369) between 2020 and 2024. Findings suggest flashcards enhance vocabulary retention, learner motivation, and classroom interaction. Digital flashcards, particularly those utilizing spaced repetition technology, offer advantages in accessibility and long-term retention, although challenges such as digital literacy gaps and over-reliance on rote memorization persist. While flashcards effectively support vocabulary learning, their integration with contextual and communicative learning strategies is crucial for maximizing their pedagogical benefits. The review highlights the importance of a balanced approach in incorporating flashcards within ELT and suggests future research on their role in higher-order language skills development.